7 - The Youth and Political Ideology in Ghanaian Politics: The Case of the Fourth Republic - Van Gyampo, Ransford Edward (Africa Development, 2021)
The youth of Ghana have played an important role in both local and national politics since the inception of the Fourth Republic. Among other things, they have served as the foot-soldiers and channels through which party manifestoes have been transmitted to the electorate and polling agents during registration and voting exercises. Through chanting of their party slogans and house-to- house campaign, the youth have often made the presence of their various parties felt across the country. In developed democracies, one key factor that motivates the youth in playing active role in politics is political ideology. This is because political ideology largely shapes the political future of the youth, especially students in tertiary institutions. Unfortunately, a brief survey shows that political ideology, though relevant, contributes little in whipping up support for political parties among the youth. The article discusses the reasons for the seeming irrelevance of political ideology among the youth. It recommends massive campaign by political parties to educate the youth on their respective political ideologies, their relevance and the need to uphold them. It also stresses the need for party leaders themselves to insist on ideological purity in all th ir dealings with other parties to serve as an example for the youth to emulate.